"Come through the water, come through the flood": black women's gospel practices and social critique - Fulton Minor, DoVeanna S. (The journal of religion & society, 2011)
This article explores gospel music created by Black women as a form of protest that critiques social injustice. Using the tragic circumstances the 1927 Mississippi River Flood, the author argues that in the first half of the twentieth century the emergent gospel music became a vehicle through which African American women could circumvent the restrictive gender dictates of Black churches. In music created immediately following the flood and years later, Black women challenged the rhetoric and practice of hegemony through an alternative oral discourse that recognized the whole self as integral to spiritual and subjective fulfillment, and simultaneously critically assessed their cultural milieu.